2004
DOI: 10.1017/s0031182004005906
|View full text |Cite
|
Sign up to set email alerts
|

Human infectivity trait in Trypanosoma brucei: stability, heritability and relationship to sra expression

Abstract: Email: m.turner@bio.gla.ac.ukT SUMMARY Some Trypanosoma brucei lines infect humans whereas others do not because the parasites are lysed by human serum. We have developed a robust, quantitative in vitro assay based on differential uptake of fluorescent dyes by live and dead trypanosomes to quantify the extent and kinetics of killing by human serum. This method has been used to discriminate between three classes of human serum resistance; sensitive, resistant and intermediate. TREU 927/4, the parasite used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Several mechanisms have been described to account for T. b. rhodesiense and T. b. gambiense resistance to TLF-1 [17–19]. Most T. b. rhodesiense isolates express the SRA gene and that is sufficient to confer resistance to TLF-1 and normal human serum [23]. Found primarily within endosomal vesicles in T. b. rhodesiense , SRA co-localizes with TLF-1 following endocytosis and the two molecules traffic together to the lysosome [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been described to account for T. b. rhodesiense and T. b. gambiense resistance to TLF-1 [17–19]. Most T. b. rhodesiense isolates express the SRA gene and that is sufficient to confer resistance to TLF-1 and normal human serum [23]. Found primarily within endosomal vesicles in T. b. rhodesiense , SRA co-localizes with TLF-1 following endocytosis and the two molecules traffic together to the lysosome [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a T.b. brucei reference strain (TREU927/4) that was recently observed as partially resistant to human serum and yet the SRA gene is not detectable by PCR (Radwanska et al, 2002;Turner, 2004;Vanhamme, 2004). A number of genes with homology to SRA have been identifiable which are unable to confer resistance to human serum (Turner, 2004;Vanhamme, 2004), the ease to apply SRA-PCR and short time taken to define the risk of the animal reservoir makes it become a technique of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Although compelling evidence supports the role of SRA in human infectivity by T. b. rhodesiense, several investigators have reported the occurrence of human serum-resistant lines of African trypanosomes that lack the SRA gene (2,47,66,67). To investigate the mechanism of SRA-independent resistance, we generated human serum-resistant lines of T. b. brucei 427 (MiTat 1.2) by repeated in vitro exposure to human HDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about ESAG1, but it is predicted to be a transmembrane cell surface protein in bloodstream trypanosomes (44). While the function of each of these proteins is unknown, it is interesting to note that another human serum-resistant line of T. b. brucei (TREU 927; GuTat 10.1) also lacks these genes in the active expression site (66,67).…”
Section: Discussionmentioning
confidence: 99%